Liquidity and the dynamic pattern of asset price adjustment: A global view - Belke, Ansgar; Orth, Walter; Setzer, Ralph (Journal of Banking & Finance, 2010)
Global liquidity expansion has been very dynamic since 2001. Contrary to conventional wisdom, high money growth rates have not coincided with a concurrent rise in goods prices. At the same time, however, asset prices have increased sharply, significantly outpacing the subdued development in consumer prices. We investigate the interactions between money and goods and asset prices at the global level. Using aggregated data for major OECD countries, our VAR results support the view that different price elasticities on asset and goods markets explain the observed relative price change between asset classes and consumer goods.